USO DE Drosophila melanogaster COMO MODELO PARA O ESTUDO DO RELÓGIO CIRCADIANO EM INSETOS VETORES - Amoretty, Paulo Roberto de; Padilha, Karine Pedreira; de Freitas, Rayane Teles; Bruno, Rafaela Vieira (Acta Scientiae et Technicae, 2013)
The last decades have established D. melanogaster as the main multicellular model organism, and many researchers have been attracted to work with this insect due to its potential of combining a genetic and mollecular approach to investigate genetic expression, celullar biology and neurobiology. In this paper we discuss the use of this organism model in the study of the circadian clock in insect vectors.